ПЕРЕДАЧА ОБСЛУГОВУВАННЯ В WIMAX/LTE НА БАЗІ IMS-АРХІТЕКТУРИ - Семендяк, Євгеній Сергійович; Кравчук, Сергій Олександрович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
An IMS-based integration architecture for WiMAX/LTE handover To provide users with always-on connectivity, researchers have tackled the issue of the integrating beyond 3G networks such as 3GPP Long Term Evolution LTE and non-3GPP networks. In this context, was proposed an integration architecture for WiMax and LTE access technologies based on EPC as core network and IMS for service provisioning.